Identify the causal pattern of sustainability principles Environment Based on Leed Regulations with Emphasis on Traditional Iranian Architecture (Case Study: Qom City) - Hassan Haji Amiri; Arash Seghfi Asl; Mehdi Ashjaie (تحقیقات کاربردی علوم جغرافیایی)
The question of resource constraints is an issue for all industrialized, developed and developing countries. Therefore, saving on fossil energy consumption and sustainable development have become very important and common issues internationally. So as to conserve energy resources, prevent contamination of the land and the environment, reduce fossil energy use and co-exist with natural and state-of-the-art environments, one of the most important measures in architecture and urban planning, and the architects and urban planners have to adhere to the principles and rules. Special in the field of construction. Over the years, various guidelines, standards, and standards have been developed to optimize energy consumption in buildings, including the most noteworthy metrics today (LEED). The purpose of the present study is to identify the causal pattern of environmental sustainability principles based on the Leid's Code. The present study is of applied purpose and of descriptive-analytical method. The statistical population of this study consisted of Qom architects and experts. The sample size was 25 individuals. In order to achieve the purpose of the study, fuzzy DEMATEL model was used. The results of this study showed that amongst the biodiversity sustainability criteria based on the Leading Model of the Sustainable Site Criterion was identified as the most influential criterion and the Regional Priority and Innovation Criteria in the design as the most influential criterion. Energy, climate and water efficiency and indoor air quality of materials and materials were also identified as intermediate criteria.